Jabberwocky [videorecording (DVD)] - Gilliam, Terry; Gilliam, Terry; Palin, Michael; Corbett, Harry H.; Carroll, Lewis, 1832-1898 (Criterion collection, 2017)
A witless, bumbling young peasant is mistaken for the man the townspeople are expecting to save the kingdom from a terrible dragon.